Influence of Psychoactive Substance use on Students’ Self-esteem among Nasarawa State University Undergraduate, Keffi (Global Journal of Human-Social Science, 2021)
This study examine the Influence of psychoactive substance use on students self-esteem among Nasarawa State University Undergraduate Keffi 100 participants were randomly selected from four different departments of Nasarawa state university keffi they include Political Science Department History Department Christian Religious Studies Department and Geography Department out of which 50 were males and 50 were females their age ranged from 8-40 years The purpose of the study is to examine whether male indulge in psychoactive substance use than female and to also investigate the degree of self-esteem of students and the possible cause of psychoactive substance use among students Data were collected using questionnaire and chi-square statistics was used for data analysis The result shows that there will be a significant difference in self-esteem of male and female in the perception of substance X2 0 25 df 1 p 0 05 and Student with high self-esteem will have significantly more negative perception of psychoactive substance use than students with low self-esteem at X2 1 8 df 1 p 0 05
Keywords: psychoactive; substance use; self-esteem